Maleficent [videorecording (DVD)] - Jolie, Angelina, 1975-; Fanning, Elle, 1998-; Copley, Sharlto, 1973-; Staunton, Imelda, 1956- (Disney DVD., 2014)
A beautiful, pure-hearted young woman, Maleficent has an idyllic life growing up in a peaceable forest kingdom, until one day when an invading army threatens the harmony of the land. Bent on revenge, Maleficent faces a battle with the invading king's successor and, as a result, places a curse upon his newborn infant Aurora. As the child grows, Maleficent realizes that Aurora holds the key to peace in the kingdom, and perhaps to Maleficent's true happiness as well.